Enhanced thermal sensitivity in single metal thermocouple: significance of thickness-engineering of the metal layers - Rafiq Mulla (Engineering Research Express, 2021)
Single metal thermocouples (SMTs) have recently been developed with a new design concept of width-engineering of metal segments. In such designs, two segments of different micro-width are formed to obtain different levels of Seebeck effects. The variations in the Seebeck effect achieved from dissimilar segment width are small. In addition, the fabrication of such micro-width patterns requires special fabrication facilities such as photolithography or electron-beam lithography. In this paper, an alternative method is presented that has the potential to give high thermal sensing SMTs and requires no sophisticated facilities to fabricate. The method is based on thickness-engineering instead of width-engineering, and thus devices can be obtained from commonly available thin film deposition techniques. Constructing better thermal sensing SMTs is possible with this approach as thickness can be easily and conveniently varied down to nanoscale range which is necessary to achieve significant changes in the Seebeck effects from effectively utilizing size effects. As a result, a high thermal sensing bismuth based-SMT has been fabricated with a sensitivity of as high as 31 μV K−1, one of the highest values reported for SMTs. It is straightforward, more convenient over width-engineering approach and thus SMTs can be easily developed.